Sistem Pengendalian Internal Penerimaan Kas Studi Kasus pada Rumah Sakit ABC - Nurul Fauziah; Dewi Amalia (IPM2KPE, 2024)
This study aims to evaluate the internal control system for cash receipts at ABC Hospital by comparing it with the framework proposed by the Committee of Sponsoring Organizations (COSO). Good internal control is considered crucial for a company to achieve its goals and maintain the security of its cash assets. A qualitative research method with a comparative descriptive approach was used, with primary data collected through observation. The results of the observation analysis show that although internal control over cash receipts at ABC Hospital is effective, there are several aspects that need improvement, such as the need for written procedures and official policies regarding cash receipts and disbursements. In addition, problems occur in processing information and documents when there is a power outage or an error in the hospital management information system. Conclusion, that certain improvements are needed to ensure the efficiency and security of the cash receipts internal control system. Keywords: Cash Receipts, Internal Control System, Accounting Information System